Louisburg Square, ca. 1870-1900 - Unknown (Tufts Archival Research Center, 2005)
Street-level view northwest of Louisburg Square, located between Mt. Vernon Street to the south-southeast and Pinckney Street to the north-northwest. Houses lining the west side of Louisburg Square are visible in the left-half of the photograph. Houses lining the north-northwest side of Pinckney Street are visible along the right side of the photograph. A wrought iron fence encircles a park located in the center of Louisburg Square. Two statues, one of Aristides and the other of Christopher Columbus, are visible in the park. A street-lamp is located on the southeast corner of Mt. Vernon Street and Louisburg Square. Copyprint; development plan for Louisburg Square designed by Stephen P. Fuller, 1826; houses located at Louisburg Square built, 1834-48; statues donated by Joseph Iasigi, 1850 4 7/8 x 7 3/4 Photographs